Evaluasi Kinerja Berdasarkan Implementasi Sistem Pengendalian Internal - D. Divianto; F. Febrianty (Akuntabilitas, 2017)
The purpose of this study is to evaluate the performance based on the implementation of Internal Control System (SPI) at the Sub-Branch Office of Bank XYZ Palembang. The sample in this study were 48 respondents of the Sub-Branch Office of Bank XYZ Palembang. Data analysis technique used is descriptive qualitative method through descriptions of recapitulation result of respondent's answer on research questionnaire. The results of this study indicate that performance management has started supported by the application of SPI is considered adequate. However, the limited implementation of performance appraisal for financial elements causes SPI performance for the completion of follow-up audit findings at the Branch Office is not considered optimal. Therefore, attention needs to be applied to the SPI which also focuses on non-financial elements that also greatly support the company's performance either directly or indirectly. This research is expected to provide a description of the correlation between company performance with effective and efficient SPI implementation especially related to the completion of follow up on audit findings.